2014
DOI: 10.5755/j01.ee.24.5.3920
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Reputation Management Decisions: Customer’s Perspective

Abstract: When corporate reputation is analyzed from the perspective of relationship equity and communication, the analysis frequently appeals to expectations and experience of customers as the most important group of stakeholders. Yet in practice there are no methodologies of corporate reputation management of this kind that could be easily adapted and would capture the impact of reputation management decisions for sustainable customer confidence in the organization. Therefore, the research problem is structured as a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…It also provides management insight with respect to the need for internal communication within hospitality organizations to be smooth and dynamic in order to maximize the expected benefits. Researchers argued that communication have to be considered as a critical component of CR (Benthaus et al, 2013;Guru et al, 2013;Matuleviciene and Stravinskiene, 2016;Petrokaite and Stravinskiene, 2013;Podnar et al, 2012), as it is based on hospitality service excellence which is to be created by the informed hospitality employees. Furthermore, Forman and Argenti (2005), while they were testing whether the effective communication impacts on CR or not, have concluded that CR arises primarily from how organization represents itself.…”
Section: Discussionmentioning
confidence: 99%
“…It also provides management insight with respect to the need for internal communication within hospitality organizations to be smooth and dynamic in order to maximize the expected benefits. Researchers argued that communication have to be considered as a critical component of CR (Benthaus et al, 2013;Guru et al, 2013;Matuleviciene and Stravinskiene, 2016;Petrokaite and Stravinskiene, 2013;Podnar et al, 2012), as it is based on hospitality service excellence which is to be created by the informed hospitality employees. Furthermore, Forman and Argenti (2005), while they were testing whether the effective communication impacts on CR or not, have concluded that CR arises primarily from how organization represents itself.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, agent in the world of right proves his competence and shows his success as required, thus creating confidence in trustor’s side (Petrokaite and Stravinskiene, 2013). This functional reputation is proven in the relation with performance purpose from various functional systems (politics, economy and others).…”
Section: Trust and Reputationmentioning
confidence: 99%
“…Therefore, the process begins with the definition of strategic inputs, such as vision and mission, and also of environmental and social responsibility. The appropriate sustainability strategy can then be defined, and the company"s strategic goals as well as the connections between them derived there (for further discussion, see also Kraus & Lind, 2012;Ubius & Alas, 2012;Petrokaite & Stravinskiene, 2013 …”
Section: Customersmentioning
confidence: 99%